Measuring Physical Inactivity: Do Current Measures Provide an Accurate View of “Sedentary” Video Game Time? - Simon Fullerton; Anne W. Taylor; Eleonora Dal Grande; Narelle Berry (Journal of Obesity)
Background. Measures of screen time are often used to assess sedentary behaviour. Participation in activity-based video games (exergames) can contribute to estimates of screen time, as current practices of measuring it do not consider the growing evidence that playing exergames can provide light to moderate levels of physical activity. This study aimed to determine what proportion of time spent playing video games was actually spent playing exergames. Methods. Data were collected via a cross-sectional telephone survey in South Australia. Participants aged 18 years and above (n=2026) were asked about their video game habits, as well as demographic and socioeconomic factors. In cases where children were in the household, the video game habits of a randomly selected child were also questioned. Results. Overall, 31.3% of adults and 79.9% of children spend at least some time playing video games. Of these, 24.1% of adults and 42.1% of children play exergames, with these types of games accounting for a third of all time that adults spend playing video games and nearly 20% of children’s video game time. Conclusions. A substantial proportion of time that would usually be classified as “sedentary” may actually be spent participating in light to moderate physical activity.